1987
DOI: 10.1128/aac.31.5.752
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant bovine alpha 1 interferon in reducing respiratory disease induced by bovine herpesvirus type 1

Abstract: Intranasal or intramuscular treatment of calves with recombinant bovine alpha, interferon before challenge with bovine herpesvwrus type 1 and Pasteurella haemolytica reduced clinical signs, number of sick days, lung lesions, and weight loss. The effective dose was determined to be relatively broad within the range of 1 to 50 mg per animal. No adverse effects were observed even at high doses of interferon (50 mg per animal). Administration before virus infection was more effective than administration at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…It has been reported that viral bacterial synergy is greatest on day 4 following BHV-1 infection (Babiuk et al, 1985(Babiuk et al, , 1987Yates et al, 1983). The molecular basis of this fatal synergy has not been characterized.…”
Section: Disease Outcome Animal Grouping and Clinical Responsesmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that viral bacterial synergy is greatest on day 4 following BHV-1 infection (Babiuk et al, 1985(Babiuk et al, , 1987Yates et al, 1983). The molecular basis of this fatal synergy has not been characterized.…”
Section: Disease Outcome Animal Grouping and Clinical Responsesmentioning
confidence: 93%
“…This interaction is referred to as viral-bacterial synergy, and is now recognized in a wide variety of species after first being characterized following human influenza epidemics (Shope, 1931). Viral-bacterial synergy is an important factor in fatal BRD and a variety of viral (bovine herpesvirus-1, parainfluenza virus-3, bovine viral diarrhea virus, and respiratory syncytial virus) and bacterial (Mannheimia haemolytica, Haemophilus somnus, Pasteurella multocida, and Mycoplasma bovis) pathogens have been implicated in this disease complex (Babiuk et al, 1987;Booker et al, 2008;Gershwin et al, 2005;Jericho et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We initiated an analysis of the potential interactions among multiple stressors during BRD by using the disease model of a primary BHV-1 respiratory infection followed by an aerosol challenge with M. haemolytica. This disease model induces clinical signs of respiratory disease in all calves with a mortality rate of 30-70% [3]. A combination of social reorganization (abrupt separation of calf and dam) and transportation was compared to transportation alone immediately prior to BHV-1 infection, and the severity of a secondary M. haemolytica challenge was then monitored through clinical signs and mortality.…”
Section: Interaction Between Stress and Viral-bacterial Synergy In Brdmentioning
confidence: 99%
“…Проведені клінічні випробування препаратів генно-інженерних інтерферонів по-казали їх ефективну захисну дію проти низки захворювань ВРХ. Так, позитивні результати застосування рекомбінантного бичачого інтер-ферону були одержані у випадках інфікування телят вірусом діареї ВРХ [43], вірусом герпесу типу 1 [7], вірусом коров'ячої віспи [104], збуд-никами, що викликають респіраторні захворю-вання [4] та бактеріальні інфекції [92]. Захист організму свиней від дії вірулентного вірусу ящуру було продемонстровано при застосуван-ні різних видів рекомбінантного свинячого ін-терферону -альфа, бета та гамма [27,79,80].…”
Section: The Information About the Use Of Interferons In Veterinary Munclassified